Archaea New Biocatalysts, Novel Pharmaceuticals and Various Biotechnological Applications - Sghaier, Haitham; Najjari, Afef; Ghedira, Kais (IntechOpen, 2017)
Besides the Introductory Chapter that gives a brief overview of archaeal applications, the present book contains four chapters. The first chapter, by Castro-Fernandez et al., provides an interesting depiction of the phylum Euryarchaeota and its biotechnological applications. The second chapter, by Ben Hania and coauthors, focuses on the promotion of the idea that some specific Archaea are potential next-generation probiotics. The third chapter, by Torregrosa-Crespo et al., emphasizes the main characteristics of biocompounds from haloarchaea and their potential uses in biomedicine, pharmacy, and industry. The concluding chapter, by Mizuno et al., proposes a plasmid curing approach for improving the potential of thermophiles in various biotechnological applications and opens new perspectives on industrial valorization.